Use of anabolic substances in culled cows - Salomoni, Eduardo; Borba, Eber Rosa (Pesquisa Agropecuaria Brasileira, 2014)
The experiment was conducted at Unidade de Execução de Pesquisa de Âmbito Estadual de Bagé (UEPAE de Bagé/EMBRAPA), at Bagé RS, Brazil. The experimental animals were 35 Ibagé (3/8 Nelore – 5/8 A. Angus) culled cows from the Station herd. They were randomly assigned and submitted for 209 days to the folowing treatments in a completely randomized statistical design: Treatment I - Control; Treatment II - lmplant of 36 mg of Zeranol sixty-days intervals. Total of three implants; Treatment III - Implant of 36 mg of Zeranol at ninety-days intervals. Total of two implants. During the experimental period the animals grazed on a natural grassland area at the stocking rate of one head per ha. The treatment effects were determined on the basis of weight gain and carcass yield, and income by net return (gross income minus cost). The utilization of Zeranol did not improve the weight gain over the whole experimental period (209 days) but the gains obtained in the 30, 60 and 90 days which immediately followed the first implant were superior to the control (P < 0.01). The net return for Zeranol treatments was inferior to the control due to a lesser amount paid for the kilogram of carcass and higher variable costs.